Sports physiology - An upcoming avenue - Ruchi Kothari; Snigdha Sharma (Wolters Kluwer Medknow Publications, 2019)
The physiology of sports embodies a wide and diverse range of scientific interests. It is a recent outlet emanating from the discipline of exercise physiology that encompasses application of the concepts of exercise physiology to training athletes and enhancing sports performance. Sports physiology, a field that was once pursued almost exclusively in research laboratories and cardiac rehabilitation programs, is now commonly applied in comprehensive sports medicine clinics. Cardiorespiratory fitness is one of the most important parameters of physical fitness of an individual. This can be evaluated by assessing aerobic capacity (VO2max) and heart rate variability indices signifying the cardiac autonomic sympathovagal regulation. Both of these parameters derived from cardiorespiratory fitness assessment have been found sensitive to training effects in team sports players, thus of relevance in sports physiology.